2020
DOI: 10.1007/s10072-020-04890-9
|View full text |Cite
|
Sign up to set email alerts
|

Life with chronic pain during COVID-19 lockdown: the case of patients with small fibre neuropathy and chronic migraine

Abstract: Objective We aimed at investigating the impact of COVID-19-related distress on patients with chronic pain, highlighting the effects of changes in individual habits and public health care reconfiguration on physical and psychological health. Methods During the pandemic, 80 participants (25 patients with small fibre neuropathy (SFN), 42 patients with chronic migraine (CM) and 13 patients’ healthy family members (HFM)) were asked to evaluate their COVID-19 complains, changes in habits and clinical management, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 39 publications
(48 reference statements)
2
52
2
Order By: Relevance
“…Several studies have investigated the influence of lockdown on the behaviour and habits of individuals with migraine and have explored ways in which the new circumstances have altered exposure to typical migraine triggers and migraine-aggravating behaviours 1 – 4 . Interestingly, the results of a recent study by Verhagen et al 1 suggest that, in some ways, the change in lifestyle caused by the pandemic has been beneficial for individuals with migraine.…”
mentioning
confidence: 99%
“…Several studies have investigated the influence of lockdown on the behaviour and habits of individuals with migraine and have explored ways in which the new circumstances have altered exposure to typical migraine triggers and migraine-aggravating behaviours 1 – 4 . Interestingly, the results of a recent study by Verhagen et al 1 suggest that, in some ways, the change in lifestyle caused by the pandemic has been beneficial for individuals with migraine.…”
mentioning
confidence: 99%
“…Moreover, the higher levels of disability were associated with suffering from changes in the neurologist-patient relationship. Patients with migraines during the COVID-19 pandemic complained of agitation and anxiety [ 14 ]. Patients with chronic diseases suffered from changes in medical care during the COVID-19 pandemic and need frequent access to health facilities, including in-person visits, follow-ups, and treatments [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the personal situation of the patients, particularly related to stress, working, and quality of sleep, frequency of headache could vary differently. In association with this personal situation, it has been reported that quality of life has been reduced in patients with chronic migraine during the COVID-19 lockdown in comparison with healthy family members (controls) [15]. Despite aggravating factors such as stress, exposure to work, and poor quality of sleep, the onabotulinumtoxinA treatment presented a positive effect in the patients with the planned follow-up compared to those with involuntary delay.…”
Section: Discussionmentioning
confidence: 98%